The Effect of Process Innovation on Business Performance and Role of Design Management: A Structural Equation Modelling - Al-Shorman, Mohammad; Alzoughool, 2Sameer A A; qatawneh, Diaa Khalaf Ahmed Al; Alqudah, Tamer Hussein Ahmad; Alzeer, 5Amer Jamil Mahmoud (International Journal of Psychosocial Rehabilitation, 2020)
The products industries will remain innovative in the current era of innovation and strive to produce goods and process products by handling their innovations correctly in order to succeed and stay profitable. In addition, products industries were also blamed for not having embraced product design attitude to boost business performance, while it is viewed as an integral part of process innovation. However, product industries in Malaysia are not achieving better business performance due to lack of process innovation orientation through design management activities. Hence, the main objective of this study is to test the mediating effect of design management on the relationship between process innovation and business performance of product industries in Malaysia. The quantitative research design approach was used in this study to collect data from 386 respondents selected from the product industries in Malaysia. The required data were obtained using simple random sampling by a validated questionnaire. Furthermore, the data collected from the survey were analyzed using Structural Equation Modelling (SEM). The results of this study showed that there is a significant relationship between process innovation and design management with business performance as well as design management mediate the relationship between process innovation and business performance of product industries in Malaysia. In addition, the study has established the key points that might lead to better business performance, which will benefit the product industries in the future.